Inferring global upper-mantle shear attenuation structure by waveform tomography using the spectral element method. Issue 3 (29th January 2018) - Karaoğlu, Haydar; Romanowicz, Barbara
SUMMARY: We present a global upper-mantle shear wave attenuation model that is built through a hybrid full-waveform inversion algorithm applied to long-period waveforms, using the spectral element method for wavefield computations. Our inversion strategy is based on an iterative approach that involves the inversion for successive updates in the attenuation parameter ($δ Q^{-1}_μ$ ) and elastic parameters (isotropic velocity VS, and radial anisotropy parameter ξ) through a Gauss–Newton-type optimization scheme that employs envelope- and waveform-type misfit functionals for the two steps, respectively. We also include source and receiver terms in the inversion steps for attenuation structure. We conducted a total of eight iterations (six for attenuation and two for elastic structure), and one inversion for updates to source parameters. The starting model included the elastic part of the relatively high-resolution 3-D whole mantle seismic velocity model, SEMUCB-WM1, which served to account for elastic focusing effects. The data set is a subset of the three-component surface waveform data set, filtered between 400 and 60 s, that contributed to the construction of the whole-mantle tomographic model SEMUCB-WM1. We applied strict selection criteria to this data set for the attenuation iteration steps, and investigated the effect of attenuation crustal structure on the retrieved mantle attenuation structure. While a constant 1-D Q μ model with a constant value of 165 throughout the upper mantle was used as starting model for attenuation inversion, we were able to recover, in depth extent and strength, the high-attenuation zone present in the depth range 80–200 km. The final 3-D model, SEMUCB-UMQ, shows strong correlation with tectonic features down to 200–250 km depth, with low attenuation beneath the cratons, stable parts of continents and regions of old oceanic crust, and high attenuation along mid-ocean ridges and backarcs. Below 250 km, we observe strong attenuation in the southwestern Pacific and eastern Africa, while low attenuation zones fade beneath most of the cratons. The strong negative correlation of $Q^{-1}_μ$ and VS anomalies at shallow upper-mantle depths points to a common dominant origin for the two, likely due to variations in thermal structure. A comparison with two other global upper-mantle attenuation models shows promising consistency. As we updated the elastic 3-D model in alternate iterations, we found that the VS part of the model was stable, while the ξ structure evolution was more pronounced, indicating that it may be important to include 3-D attenuation effects when inverting for ξ, possibly due to the influence of dispersion corrections on this less well-constrained parameter.